Bioavailability and metabolism of orange juice flavanones in humans: Impact of a full-fat yogurt - Mullen, W.; Archeveque, M.; Edwards, Christine; Matsumoto, H.; Crozier, A. (American Chemical Society, 2008)
The bioavailability of dietary phytochemicals may be influenced by the food matrix in which they are consumed. In this study the impact of a full-fat yogurt on the bioavailability and metabolism of orange juice flavanones was investigated. Human plasma and urine were collected over a 24 h period after the consumption of 250 mL of orange juice containing a total of 168 µmol of hesperetin-7-O-rutinoside and 12 µmol of naringenin-7-O-rutinoside, with and without 150 mL of full-fat yogurt. The juice also contained 1 g of paracetamol and 5 g of lactulose. HPLC-MS2 analysis revealed the accumulation of hesperetin-7-O-glucuronide, and an unassigned hesperetin-O-glucuronide metabolite in plasma reached a peak concentration (Cmax) of 924 ± 224 nmol/L, 4.4 ± 0.5 h (Tmax) after orange juice ingestion. The Tmax is indicative of absorption in the colon. When the juice was consumed with yogurt, neither the Cmax at 661 ± 170 nmol/L nor the Tmax at 5.1 ± 0.4 h were significantly different from those obtained with juice alone. The two hesperetin glucuronides were also excreted in urine along with a third hesperetin-O-glucuronide, two hesperetin-O-glucuronide-O-sulfates, a hesperetin-O-diglucuronide, a naringenin-O-diglucuronide, and, tentatively identified, naringenin-7-O- glucuronide and naringenin-4'-O-glucuronide. This indicates the occurrence of substantial, postabsorption, phase II metabolism prior to urinary excretion. The quantity of flavanone metabolites excreted 0-5 h after orange juice ingestion was significantly reduced by yogurt, but over the full 0-24 h urine collection period, the amounts excreted, corresponding to ca. 7.0% of intake, were not affected by the addition of yogurt to the drink. Nor did yogurt have a significant effect on gastric emptying, as determined by plasma paracetamol levels, or on the mouth to cecum transit time of the head of the meal, assessed by measurement of lactulose-derived breath hydrogen. There is also a discussion of the merits of studies of the absorption and metabolism of flavanones based on direct analysis of metabolites by HPLC-MS and the more traditional indirect approach where samples are treated with a mollusc glucuronidase/sulfatase preparation prior to HPLC analysis of the released aglycones. © 2008 American Chemical Society.